Defining bovine CpG epigenetic diversity by analyzing RRBS data from sperm of Montbéliarde and Holstein bulls - Capra, Emanuele; Lazzari, Barbara; Cozzi, Paolo; Turri, Federica; Negrini, Riccardo; Ajmone-Marsan, Paolo; Stella, Alessandra (Frontiers in Cell and Developmental Biology, 2025)
IntroductionBreed epigenetic diversity was recently detected in pig muscle and cattle blood, probably as a result of long-term selection for morphological adaptive and quantitative traits, persisting after embryo epigenetic reprogramming.MethodsIn our study, breed epigenetic diversity in the male germline from Holstein (H) and Montbéliarde (M) bulls was investigated using Reduced Representation Bisulfite Sequencing (RRBS) data publicly available at the NCBI database. Open-source Whole Genome Sequencing (WGS) data from H and M animals were used to estimate genetic diversity between the two breeds and, thus, correctly assess CpG positions with low frequencies or absence of SNPs.ResultsSperm epigenetic diversity was studied in 356,635 SNP-free CpG positions, and a total of 6,074 differentially methylated cytosines (DMCs) were identified. The analysis of the DMCs pattern of distribution revealed that DMCs: i) are partially associated with genetic variation, ii) are consistent with epigenetic diversity previously observed in bovine blood, iii) present long-CpG stretches in specific genomic regions, and iv) are enriched in specific repeat elements, such as ERV-LTR transposable elements, ribosomal 5S rRNA, BTSAT4 Satellites and long interspersed nuclear elements (LINE).DiscussionThis study, based on publicly available data from two cattle breeds, contributes to the identification and definition of distinct epigenetic signatures in sperm, that may have potential implications for mammalian embryo development.